Obituary: Hans Cory, O.B.E. 1889-1962 - Tracey, Hugh (International Library of African Music, 1962)
HANS CORY was an extraordinary person in so many ways. Born in Vienna and an early student of Freud, he came to Africa at Freud's request to study the dreams of Africans in what was then German East Africa. Caught up by the 1914-1918 war, Hans Cory spent several years in a prison camp in Palestine but returned to Tanganyika to grow sisal. This was not his true vocation and it was not long before his outstanding capacity tor understanding the special and particular mentality of African communities led him into sociology. Hans Cory was one of the first, if not the first, to make a collection of Sukuma and Nyamwezi songs and he always regretted not having more time to devote to their music.
Keywords: African Music